Pengembangan Sistem Customer Relationship Management (CRM) Berbasis Web Dengan Workflow Dinamis Untuk Peningkatan Proses Penjualan - Fadilah, Muhamad Akbar; Ratna Yulika Go; Hermansyah; Imam Sutanto (AI Society & STMIK Indonesia, 2025)
The limitations of conventional static and inflexible Customer Relationship Management (CRM) systems have resulted in significant challenges in adapting to the specific needs of various types of businesses, with PerFormance being restricted in terms of flexibility to adapt to market changes. After implementing a CRM system with a static Workflow, PT Rintis Sejahtera recorded significant improvements, such as a 35% increase in customer request handling speed and a 28% increase in customer satisfaction. This research aims to develop a web-based CRM system with dynamic Workflows that can enhance operational Efficiency and effectiveness, allowing it to adapt to future changes. The study focuses on implementing web technologies to design and develop a CRM system capable of adjusting Workflows according to the specific needs of the user company. The research methodology used in this study includes the PIECES framework and the Waterfall model. The PIECES approach covers aspects such as PerFormance, InFormation, Economics, Control, Efficiency, and Service, which are applied to analyze and design a better CRM system. Additionally, the Waterfall method is used to ensure that each stage of system development, from requirements analysis to testing, is carried out sequentially and systematically. The combination of these two methods aims to produce a functional system that meets user expectations. The results of the study show that the web-based CRM system with dynamic Workflows successfully improved operational Efficiency and effectiveness by 50% in customer request handling speed and 45% in customer satisfaction. System testing was conducted using the Black Box Testing method, with the evaluated indicators focusing on the Expected Results of each system function, such as respone speed, the ability to manage dynamic Workflows, and user satisfaction levels. The test results indicate that the system is fully functional and meets all expected requirements.